PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN EFIKASI DIRI (SELF EFFICACY) DAN AKTIVITAS BELAJAR SISWA KELAS XI PEMASARAN MATA PELAJARAN RITEL SMK BATIK 2 SURAKARTA - -, Amalia Rohmah -; -, Dewi Kusuma Wardani -; -, Leny Noviani - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This classroom action study aims  (1) To improve student learning activity of XI PM SMK Batik 2 Surakarta by using cooperative learning model of Student Team Achivement Division type. (2) To improve self efficacy of student of XI PM SMK Batik 2 Surakarta by using cooperative learning model of Student Team Achivement Division type.               This research is a classroom action research with two cycles and using STAD type cooperative method. This research is located in SMK Batik 2 Surakarta. Techniques and data collection tools in this study using a interview technique.               The results showed that with STAD type cooperative method there was an active and fun learning atmosphere so that the students' learning activity and self efficacy were improved. The results of the cycle I to cycle II there is an increase in self-efficacy of 62.60 to 80.86, and learning activities 70.64% and increased again in cycle II to 84.77%. It is concluded that STAD type cooperative method can improve self efficacy and student learning activities.